Adcreep : the case against modern marketing - Bartholomew, Mark, 1971- (Stanford, California : Stanford Law Books, an imprint of Stanford University Press, 2017)
Adcreep pulls back the curtain on the curious and sometimes troubling world of modern advertising. An array of techniques that might seem like the stuff of science fiction--biometric scans, automated online spies, facial recognition software--are now routinely deployed to study and stimulate consumer desire. Sometimes today's advertisers can hide in plain sight, converting historically ad-free spaces into commercial canvases by infiltrating schools and national parklands. At other times, they rely on social media to mask their role, mobilizing everyone from celerities to your friends and relatives to clandestinely convey their messages for them. Through it all, the legislators and judges charged with protecting consumers stand idly by, increasingly numb to the onslaught of commercial come-ons. The end result is that corporate America not only knows you better than ever before, but can reach you at almost any moment, often without your awareness, dramatically tilting the historical balance of power between advertiser and audience. Mark Bartholomew reveals the consequences of life in a world of nonstop selling, drawing from psychological experiments, marketing texts, communications theory, and the history of advertising. Adcreep mounts a damning critique of the modern American legal system's failure to stem the flow of invasive advertising into our homes, parks, schools, and digital lives. -- Inside jacket flap.
Advertising on trial -- Colonizing new advertising spaces -- The new market research -- From market share to mindshare -- Sellebrity -- Stopping adcreep.
Includes bibliographical references (pages 189-228) and index.
Keywords: Advertising laws -- United States; Marketing -- Law and legislation -- United States; Advertising -- Social aspects -- United States; Marketing -- Social aspects -- United States